Food processor perfection : 75 amazing ways to use the most powerful tool in your kitchen (Test Kitchen handbook, 2017)
Is your food processor gathering dust in your cabinet? This collection of recipes will harness its many powers and teach you what your multipurpose appliance can do. You'll find innovations for recipes that typically require specialty tools, and you'll also get buying advice backed by the test kitchen's in-depth testing protocols. It's like having a mechanical sous chef in your kitchen!